Identification of Avian Influenza with the Real-Time Polymerase Chain Reaction (RT‒PCR) Method - Anak Agung Ayu Sauca Sunia Widyantari; Fauzi Rahmat Kurniawan (Journal of Pharmaceutical and Health Research, 2023)
Avian influenza is a zoonotic disease transmitted from poultry to humans. The prevalence of AI disease in Indonesia is likely to be a global health threat because of the ease of mutation in each generation, which makes pathogenicity higher. However, detection efforts still use conventional methods, so a more sophisticated detection search is needed. This research aims to identify the DNA amplification process and the results of detecting avian influenza virus using real-time PCR. Qualitative research using samples from BBVet Denpasar in May 2022. The samples were analyzed using the real-time polymerase chain reaction (RT‒PCR) method, and the results obtained were analyzed descriptively. The results show that the RT‒PCR method is very effective for detecting the presence of AI quantitatively and molecularly. A graph that crosses the threshold on cycles lower than 40 indicates that a positive sample will show nominal Ct. No nominal Ct was detected in this study, and the graph did not cross the threshold, so the model tested negative for the AI virus. The DNA amplification process of the avian influenza virus begins with an amplification process of 40 cycles, with each cycle stage in the form of denaturation at 94 °C for 30 seconds, annealing at 64 °C for 60 seconds, and DNA synthesis at 76 °C for 30 seconds. One cycle is declared if the amplification process has passed these three stages.